"An Experiment in Optimism Was Coming to an End": Gift Exchange and Giftedness in Two Novels of the Occupy Era. (17th May 2022) - LAWRIE, ALEXANDRA
Abstract : This article examines the role of "gifts" and "giftedness" in two recent novels about Occupy Wall Street, Barbara Browning's The Gift and Caleb Crain's Overthrow . Together these novels explore how projects designed to offset the effects of neoliberal individualism very often end up replicating, rather than disrupting, aspects of capitalist exchange: the authors temper their own utopian impulses by interrogating the factors which prevent systemic change, such as individual complacency and governmental intervention. The article considers the cycle of gift giving launched by Browning's narrator, a project which falters because her understanding of economization is inadequate, and because she refuses to take account of her own class position. Crain's group of young Brooklynites believe that mind reading draws people together and prevents social isolation. While the vagueness of their aims can be taken as an implied narrative criticism of their impractical plans, the reason they abandon the project is because it encroaches on the government's surveillance programme, which identifies them as security threats.